2022
DOI: 10.1186/s12864-022-08747-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-trait analyses improved the accuracy of genomic prediction and the power of genome-wide association of productivity and climate change-adaptive traits in lodgepole pine

Abstract: Background Genomic prediction (GP) and genome-wide association (GWA) analyses are currently being employed to accelerate breeding cycles and to identify alleles or genomic regions of complex traits in forest trees species. Here, 1490 interior lodgepole pine (Pinus contorta Dougl. ex. Loud. var. latifolia Engelm) trees from four open-pollinated progeny trials were genotyped with 25,099 SNPs, and phenotyped for 15 growth, wood quality, pest resistance, drought tolerance, and defense chemical (mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…If a regression coefficient is equal to 1, there is no bias. A regression coefficient greater or smaller than 1 indicates inflated or deflated predictions, respectively [ 48 ]. The training and testing populations were split randomly into 80% and 20% genotypes (5-fold cross-validation).…”
Section: Methodsmentioning
confidence: 99%
“…If a regression coefficient is equal to 1, there is no bias. A regression coefficient greater or smaller than 1 indicates inflated or deflated predictions, respectively [ 48 ]. The training and testing populations were split randomly into 80% and 20% genotypes (5-fold cross-validation).…”
Section: Methodsmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) are a robust method for identifying potential causal genes or genomic regions that are associated with plant phenotypic variation (Ingvarsson & Street, 2011; Kruglyak, 2008). Several studies have successfully identified single‐nucleotide polymorphisms (SNPs) that are associated with resistances to abiotic and biotic stresses, including drought and disease resistance, in various plant species (Beaulieu et al., 2020; Bouvet et al., 2020; Cappa et al., 2022; Laverdière et al., 2022; Lenz et al., 2020; Muchero et al., 2018; Mukrimin et al., 2018; Soro et al., 2022; Stocks et al., 2019; Vázquez‐Lobo et al., 2017; Wang et al., 2019; Westbrook et al., 2020). The utilization of GWAS results can expedite the conventional breeding process and enable genotype‐based selection (Neale & Kremer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In GS, a population in which individuals are both phenotyped and genotyped is used to train a model, which is then used to predict the genetic merit of young genotyped, but unphenotyped, offspring. Selections from a large number of genotyped candidates should translate into higher selection intensities, while preserving genetic diversity in improved varieties, or allowing for efficient multi-trait selection strategies ( Bouvet et al., 2020 ; Lenz et al., 2020b ; Bousquet et al., 2021 ; Cappa et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changing environmental conditions and forest product markets are putting pressure on tree breeding programs to rapidly deliver adapted planting stock with superior end-use quality attributes. Hence, accelerating breeding for improved reforestation material is becoming essential for traits related to wood quality ( Hassegawa et al., 2020 ), biotic stress resistance ( Beaulieu et al., 2020 ; Lenz et al., 2020b ; Westbrook et al., 2020 ; Mphahlele et al., 2021 ; Gamal El-Dien et al., 2022 ), and resilience to abiotic stress such as drought ( Bouvet et al., 2020 ; Depardieu et al., 2020 ; Cappa et al., 2022 ; Laverdière et al., 2022 ; Soro et al., 2022 ). GS can hence play an active role in climate change mitigation strategies and provide more flexibility to tree breeders.…”
Section: Introductionmentioning
confidence: 99%